Performance Sensitivity and Fairness of ECN-Aware 'Modified TCP' - MISRA, Archan (Institutional Knowledge at Singapore Management University, 2003)
The paper discusses how Explicit Congestion Notification (ECN) can be used to devise a congestion control mechanism for the Internet, which is more rapidly reactive and allows best-effort flows to rapidly adjust to fluctuations in available capacity. Our ECN-mod protocol involves simple modifications to TCP behavior and leverages more aggressive marking-based router feedback.Simulations show that ECN-mod is better than TCP NewReno even for Web-style intermittent traffic sources, and makes the link utilization significantly less sensitive to the variation in the number of active flows. Simulations also show that, while ECN-mod flows obtain a larger portion of the available capacity than conventional best-effort traffic, they do not starve or significantly penalize such TCP-based flows.